Influence of initial defects on defect formation process in ion doped silicon - Smyntyna, V.A.; Sviridova, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
We study the influence of initial defects in high-resistance epitaxial silicon layers of high-resistance epitaxial silicon structures on defect formation processes at ion boron doping. The method of reverse voltage-capacitance characteristics revealed two maxima of dopant concentration in epitaxial silicon layers ion-doped by boron. Studing the structure of the near-surface area in ion-doped epitaxial silicon by means of modern methods has shown that in the field of the first concentration maximum (the nearest one to a wafer surface), the fine-blocked silicon structure is localised. In the range of the second doping concentration maximum, the grid of dislocations with the variable period within one grid and consisting of 60° dislocations is found out. In the area of dislocation grids, oxygen atoms have been found out. The variable period in the grid is related with a change of mechanical stress and deformation distribution law in the plane of dopant diffusion front as dependent on the presence of initial defects in silicon.